Personality attributes of botanic parks and their effects on visitor attitude and behavioural intentions. (April 2019) - Quintal, Vanessa Ann; Lwin, Michael; Phau, Ian; Lee, Sean
The current exploratory study conceptualizes botanic park personality and explores its effects on visitor attitude and behavioural intentions. To achieve this, a renowned botanic park in Western Australia was selected. Pen-and-paper and online surveys were self-administered to 481 local and international respondents in two main studies. Two botanic park personality attributes were identified, namely, 'excitement' and 'competence', which aligned with the destination personality literature. These attributes impacted on attitude as well as subsequent intentions to visit and recommend the botanic park for local and international respondents. Findings offer researchers a platform to advance further studies on botanic park personality that may be extended to other nature-based tourism attractions. The identified and distinctive botanic park personality attributes help to guide practitioners in shaping the positioning and differentiation strategy to attract visitors and enhance the park's financial sustainability.